Building Story Games Toward Student’s Speaking Ability - Nur Fadhillah; Andi Asrifan; Firman Saleh; Sam Hermansyah; Lababa Lababa (La Ogi : English Language Journal, 2022)
The researcher took pre-experimental method with one group pre-test and post-test design. The population of this research was the eighth grade students in academic year 2018/2019. There were 86 students spread in 3 classes (VIII Expert, VIII Excellent 1, and VIII Excellent 2) and each class consist appropriately 26-31 students. VIII Expert class was taken as the sample and the total of samples is 26 students. The data of the research was collected by using speaking test. The result of data analysis showed that there was significant difference between the students’ score after they were taught by the using building story games and before they were taught by the using building story games. It was proved by the mean score of the post-test which was higher than the mean score of pre-test (73.88>63.43). Furthermore, the result of the p-value was lower than α (0.000<0.05) which means that H0 was rejected and H1 was accepted. Based on data analysis, the research concluded that there is the use of building story games toward student’s speaking ability.